First report of human Leptospira santarosai infection in French Guiana - Hatem Kallel; Pascale Bourhy; Claire Mayence; Stéphanie Houcke; Didier Hommel; Mathieu Picardeau; Valérie Caro; Séverine Matheus (Elsevier, 2020)
Leptospirosis is a zoonotic disease with worldwide distribution. In French Guiana, a French overseas department of South America, this bacterial infection is endemic with the increase of human cases since the last 5 years. Nevertheless, the epidemiological data on the circulating infecting strain remains scarce due to the lack of specific symptoms and the used diagnostic approaches. We report a severe case of leptospirosis in a 52-years-old male, working as a street cleaner, hospitalized at the Intensive Care Unit of city capital hospital of French Guiana because of hemodynamic, neurological, renal, and respiratory failure. At ICU admission, the patient was comatose, his temperature was 37.3 °C, heart rate 104 beats per minute, blood pressure 84/45 mm Hg, and oxygen saturation 95% while under mechanical ventilation. Retrospective exploration using molecular and serological approaches from the samples allowed reporting an infection by Leptospira santarosai serogroup Sejroe serovar Hardjo. To our knowledge, this is the first human case infected with this species in French Guiana. Through these analyses, this report provides new epidemiological information about the Leptospira strains circulating in French Guiana. In particular, this emphasizes the importance of accurate diagnosis to characterize with more precision the circulating Leptospira strains in this department.